Effects of age and soccer expertise on general tests of perceptual and motor performance among adolescent soccer players - Vänttinen, T.; Blomqvist, M.; Luhtanen, P.; Häkkinen, K. (Perceptual and Motor Skills, 2010)
This study of perceptual and motor skills in soccer players was conducted on adolescent males. The goals were to monitor the development of general perceptual motor skills in nonsoccer-playing and soccer-playing groups (n = 245), to examine the relationship between physical maturity and general perceptual motor skills (n = 41), and to compare the differences in general perceptual motor skills between groups with different soccer expertise (n = 142). The measured variables were simple reaction time, peripheral awareness, eye-hand-foot coordination, and testosterone blood level. The results suggested that general perceptual motor skills improved with age, the development of these skills was related to participants` blood testosterone concentration (especially between 12 and 14 years), and general perceptual motor skills improved with soccer expertise. However, the differences between subelite and elite soccer players were not meaningful enough to encourage practitioners to test general perceptual motor skills on a large scale when evaluating the potential of young players.